Neuropedagogika wśród dyscyplin naukowych – próba doprecyzowania nazewnictwa - Chojak, Małgorzata (Studia Edukacyjne, 2020)
Chojak Małgorzata, Neuropedagogika wśród dyscyplin naukowych – próba doprecyzowania nazewnictwa [Neuropedagogy Among Scientific Disciplines – an Attempt to Clarify Terminology]. Studia Edukacyjne nr 56, 2020, Poznań 2020, pp. 369-384. Adam Mickiewicz University Press. ISSN 1233-6688. DOI: 10.14746/se.2020.56.20 In the last two decades, more and more publications pedagogical and psychological referring to research in the field of neurobiology. They appear in them new concepts and names of new disciplines such as neuropedagogy, neurodidactics or educational neuroscience and neuropsychology education. The US, the UK and Canada have attempted to standardize terminology and to clarify the scope of research across disciplines. This publication is not only an attempt to present the theoretical concept of the origin and interrelationships of newly established disciplines based on international scientific sources. The author has decided to embed analyses on the specifics of Polish terms to propose names for an interesting and new field known as Mind, Brain and Education (MBE).